From old school to open science: The implications of new research norms for educational psychology and beyond. Issue 2 (3rd April 2021) - Gehlbach, Hunter; Robinson, Carly D.
Abstract: Recently, scholars have noted how several "old-school" practices—a host of long-standing scientific norms—in combination, sometimes compromise the credibility of research. In response, other scholarly fields have developed several "open-science" norms and practices to address these credibility issues. Against this backdrop, this special issue explores the extent to which and how these norms should be adopted and adapted for educational psychology and education more broadly. Our introductory article contextualizes the special issue's goals by overviewing the historical context that led to open science norms (particularly in medicine and psychology); providing a conceptual map to illustrate the interrelationships between various old-school as well as open-science practices; and then describing educational psychologists' opportunity to benefit from and contribute to the translation of these norms to novel research contexts. We conclude by previewing the articles in the special issue.